State Arts Policy Trends and Future Prospects - Lowell, Julia F. (RAND Corporation, 2008)
This report, the final in a series of four on state arts agencies, looks at these agencies' efforts to rethink their roles and missions, reflecting on what the changes may mean for state arts policy and the structure of state arts funding. The author offers a view of what the future may hold for state arts agencies and for state arts policy if current trends and strategies continue.